If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + -4) = 14x + 1 Reorder the terms: 5(-4 + 3x) = 14x + 1 (-4 * 5 + 3x * 5) = 14x + 1 (-20 + 15x) = 14x + 1 Reorder the terms: -20 + 15x = 1 + 14x Solving -20 + 15x = 1 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -20 + 15x + -14x = 1 + 14x + -14x Combine like terms: 15x + -14x = 1x -20 + 1x = 1 + 14x + -14x Combine like terms: 14x + -14x = 0 -20 + 1x = 1 + 0 -20 + 1x = 1 Add '20' to each side of the equation. -20 + 20 + 1x = 1 + 20 Combine like terms: -20 + 20 = 0 0 + 1x = 1 + 20 1x = 1 + 20 Combine like terms: 1 + 20 = 21 1x = 21 Divide each side by '1'. x = 21 Simplifying x = 21
| 16x-18y=17 | | 16+5x=31 | | 4x+4(x-10)=600 | | 24x+12=-7 | | 5x+2x-3=13x+10 | | 5x+2x-3=13x | | 13p-18=12p-8 | | 2vx-2gt=0 | | xa^2+4x-5=0 | | 2(4x+6)=2(8+4x) | | 3x+3(10+x)=420 | | ax^2+4x-5=0 | | 12x^2-94x+70=0 | | (6+n)-3-2=7 | | 3y=-2x+6 | | 15r^2-34r-15=0 | | 15r^2-34r+-15=0 | | 9x^2y^2-16w^6= | | 2(2x+2)=2(2+2x) | | -10-5=10x+21 | | 99-3x=10x-21 | | x^2-3x-28=x^2+3x-28 | | x^6n-14x^3n+49= | | -8+2(-2n-7)=6(-8n-4)-6 | | 5x^2-7.7x-1.8=0 | | 4x+4(20+x)=6000 | | 12x-2=8x+5 | | 16x^2-10000x+90000=0 | | 2t-8-1t=-3 | | 16x+4y=152 | | 21m-49m= | | -x^2-4x+21=0 |